2010
DOI: 10.1038/sj.bjc.6606035
|View full text |Cite
|
Sign up to set email alerts
|

PBOX-15, a novel microtubule targeting agent, induces apoptosis, upregulates death receptors, and potentiates TRAIL-mediated apoptosis in multiple myeloma cells

Abstract: Background:In recent years, much progress has been made in the treatment of multiple myeloma. However, a major limitation of existing chemotherapeutic drugs is the eventual emergence of resistance; hence, the development of novel agents with new mechanisms of action is pertinent. Here, we describe the activity and mechanism of action of pyrrolo-1,5-benzoxazepine-15 (PBOX-15), a novel microtubule-targeting agent, in multiple myeloma cells.Methods:The anti-myeloma activity of PBOX-15 was assessed using NCI-H929,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 42 publications
(68 reference statements)
2
42
0
Order By: Relevance
“…Here, we show anti-cancer activity of a novel MTA compound, PBOX-15, in cell line models representing poor prognostic subgroups of ALL: relapsed childhood T-ALL (CCRF-CEM) and BCR-ABL positive adult B-ALL (SD-1). Similar to our previous studies on the effect of PBOX-15 on other cancer cell types (5,6,10), we showed that PBOX-15-induced G2/M cell cycle arrest and growth inhibition was associated with the induction of apoptosis in B-ALL and T-ALL cells. A pan-caspase pharmacological inhibitor inhibited PBOX-15-induced apoptosis in both T-ALL and B-ALL cells, while caspase-3 and 8 pharmacological inhibitors inhibited apoptosis in T-ALL cells.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Here, we show anti-cancer activity of a novel MTA compound, PBOX-15, in cell line models representing poor prognostic subgroups of ALL: relapsed childhood T-ALL (CCRF-CEM) and BCR-ABL positive adult B-ALL (SD-1). Similar to our previous studies on the effect of PBOX-15 on other cancer cell types (5,6,10), we showed that PBOX-15-induced G2/M cell cycle arrest and growth inhibition was associated with the induction of apoptosis in B-ALL and T-ALL cells. A pan-caspase pharmacological inhibitor inhibited PBOX-15-induced apoptosis in both T-ALL and B-ALL cells, while caspase-3 and 8 pharmacological inhibitors inhibited apoptosis in T-ALL cells.…”
Section: Discussionsupporting
confidence: 75%
“…A pan-caspase pharmacological inhibitor inhibited PBOX-15-induced apoptosis in both T-ALL and B-ALL cells, while caspase-3 and 8 pharmacological inhibitors inhibited apoptosis in T-ALL cells. We have recently shown caspase-8-dependent PBOX-15-induced apoptosis in CLL and myeloma cells using a pharmacological inhibitor and siRNA knockdown of caspase-8 expression (7,10). However, caspase inhibitors only partially inhibited PBOX-15-induced apoptosis suggesting that caspase-independent mechanisms are also involved in PBOX-15-induced apoptosis in ALL cells (33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other side, the role of Bim in apoptosis engaged by agents known to affect the microtubular integrity, as the spindle poisons, has been only poorly investigated so far, except for microtubular-stabilising agents as taxanes [26,27], persins [30] and for PBOX-15, a novel microtubule targeting agent [31]. Both Bim-dependent apoptosis in lymphocytes [32], non-small-cell lung cancer lines [26], kidney epithelial cells [33], and Bim-independent apoptosis in HeLa and breast cancer cells [27] have been reported, so suggesting cell specificity in paclitaxel-induced cell death.…”
Section: Discussionmentioning
confidence: 99%
“…19,30,31 Therefore, it seemed interesting to assess whether, at doses lower than those used in the assessment of cell proliferation, PBOX-15 is able to improve the sensitivity to treatment with oxaliplatin or with 5-FU. Oxaliplatin in combination with 5-Fluorouracil and leucovorin (FOLFOX) has been approved for metastatic CRC therapy.…”
Section: Discussionmentioning
confidence: 99%